Control of the Radiation Patterns Using Homogeneous and Isotropic Impedance Metasurface - Fan Yang; Zhong Lei Mei; Tie Jun Cui (International Journal of Antennas and Propagation)
We propose to control the radiation patterns of a two-dimensional (2D) point source by using impedance metasurfaces. We show that the radiation patterns can be manipulated by altering the surface impedance of the metasurface. Full-wave simulation results are provided to validate the theoretical derivations. The proposed design enjoys novel properties of isotropy, homogeneity, low profile, and high selectivity of frequency, making it potentially applicable in many applications. We also point out that this design can be implemented with active metasurfaces and the surface impedance can be tuned by modulating the value of loaded elements, like resistors, inductors, and capacitors.